High-temperature-resistant oil well cement self-repairing capsule as well as preparation and application thereof
By using microcapsules with high-temperature resistant polysaccharide shells and epoxy resin cores in the oil well cement self-repair system, the problem of poor durability in the existing technology in high-temperature environment is solved, and efficient cement matrix self-repair is achieved, which is suitable for very high-quality cement matrix self-repair. Gauge oil and gas well cementing.
Patent Information
- Application Number
- CN202410894777.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-04
- Publication Date
- 2025-02-07
AI Technical Summary
The existing oil well cement self-repair system has poor durability in high temperature environments, complex processes, high pollution and high costs, making it difficult to meet the needs of unconventional oil and gas well cementing technology.
Microcapsules with high-temperature resistant polysaccharide as shell material and epoxy resin as core material were used to prepare high-temperature resistant oil well cement self-healing capsules through the O/W/O double emulsion template method to improve their self-healing ability at high temperature.
It has achieved significant improvement in the self-repairing ability of cement substrates under high temperature environments, with a repair rate of more than 36.57%, and has no damage to cement substrates, and is suitable for a variety of complex working conditions.
Smart Images

Figure CN119390380A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a high temperature resistant oil well cement self-repairing capsule and its preparation and application. Background Art
[0002] Cementing engineering is one of the important links in the development of oil and gas resources. It achieves the purpose of isolating the oil layer, gas layer and water layer in the wellbore by injecting oil well cement between the casing and the surrounding rock formation, protecting the casing of the oil and gas well, increasing the life of the oil and gas well and increasing the oil and gas production. With the intensification of the development of unconventional oil and gas resources, higher requirements are put forward for the construction quality of cementing engineering and the quality of oil and gas resource development. However, as a brittle material, cement has poor deformation ability and low tensile strength. It is very easy to crack due to the complex underground environment and subsequent construction, resulting in failure of isolation, and even the scrapping of the oil well. In addition, in the process of unconventional oil and gas resource development, the cement ring is located in an underground environment several thousand meters deep. The underground environment is complex and the temperature is high. Conventional cement repair methods are difficult to reach, the effect is poor, and the cost is high. Therefore, the self-repair research on cement ring has extremely high economic and application value.
[0003] As one of the common self-healing technologies, microcapsule technology can break when cracks occur by encapsulating repair agents, thereby achieving the purpose of in-situ repair. In addition, microcapsule technology can select different core materials and shell materials to construct microcapsules that meet different engineering needs and engineering conditions, and is often used in the self-repair of cement-based materials. García Calvo et al. synthesized silica microcapsules containing epoxy sealing compounds. The self-repair results showed that the repair effect of a lower crack width (150μm) was better than that of a crack width of 300μm, and extending the repair time could significantly improve the repair effect. (García Calvo JL, Pérez G, Carballosa P, et al. Development of ultra-high performance concretes with self-healing micro / nano-additions[J]. Constr Build Mater, 2017, 138: 306-315.) Ma et al. prepared force-chloride ion-triggered microcapsules encapsulating PbSO4 by a two-step interfacial polymerization method, and studied the self-healing properties of cement-based composites from the perspective of mechanical properties. The results show that the force-chloride ion triggering performance of the microcapsules is good, and the mechanical property repair rate of cement-based composites with 3% microcapsules can reach 84%. (Ma Y, Ge Y, Wu R, et al. Mechanical behavior and self-healing mechanism of force-chloride iontriggered double-walled microcapsule / cement-based composites[J]. Constr Build Mater, 2022, 340: 127765.)
[0004] However, in the actual application of unconventional oil and gas well cementing engineering, the underground high temperature environment requires microcapsules to have higher high temperature resistance, and the existing self-repairing microcapsules cannot meet the application conditions of high temperature environment. The existing self-repairing capsule synthesis process is complex, highly polluting, and high cost, which hinders its application in the industry. Summary of the invention
[0005] In order to at least partially solve the shortcomings of the existing oil well cement self-repairing system, such as high pollution, high cost, difficulty in industrialization, and poor high temperature resistance, an embodiment of the present invention provides a high temperature resistant oil well cement self-repairing capsule.
[0006] As one aspect of the present invention, it relates to a high temperature resistant oil well cement self-repairing capsule: the high temperature resistant oil well cement self-repairing capsule uses high temperature resistant polysaccharide as shell material and epoxy resin as core material, wherein the core material content is 15%-50%, and the shell material content is 85-50%. The shell material content is 85-50%. The self-repairing capsule has a coating rate of more than 82.5%, an initial thermal decomposition temperature of more than 212.4°C, a repair rate of more than 36.57%, and no damage to the cement matrix.
[0007] As another aspect of the present invention, it relates to a method for preparing the above-mentioned high temperature resistant oil well cement self-repairing capsule, comprising the following steps: Step 1) Preparation of shell material aqueous phase: Add 10-40g of acid-triggered curing agent, 4-10g of interface enhancer and 3-6g of high temperature resistant shell material to 100-110g of water, stir evenly, and obtain shell material aqueous phase;
[0008] Step 2) Preparation of repair agent oil phase 1: Add 20-27 g of active diluent to 90-100 g of cement self-repairing agent, stir evenly, and obtain repair agent oil phase 1;
[0009] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 20-75:80-25 to obtain a uniform oil / water emulsion;
[0010] Step 4) Preparation of oil phase 2: Add 20-30 g of surfactant to 90-100 g of paraffin oil and stir evenly to obtain oil phase 2;
[0011] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 75-80:25-20 to obtain a uniform oil / water / oil template emulsion;
[0012] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: dripping the triggering agent drop by drop into the oil / water / oil template emulsion obtained in step 5), stirring until the droplets are formed, and obtaining high temperature resistant oil well cement self-repairing capsules.
[0013] In the step 1), the acid-triggered curing agent is aluminum carbonate or aluminum hydroxide; the interface enhancer is nano zinc oxide or silica sol; and the high temperature resistant shell material is gelatin or carrageenan.
[0014] In the step 2), the active diluent is polypropylene glycol diglycidyl ether or phenyl glycidyl ether; and the cement self-healing agent is phenolic epoxy resin, bisphenol S epoxy resin or aliphatic epoxy resin.
[0015] In the step 4), the surfactant is Span-80, Span-20 or Span-85; and the trigger is dilute hydrochloric acid, dilute sulfuric acid or glacial acetic acid.
[0016] As another aspect of the present invention, it relates to the application of the above-mentioned high temperature resistant oil well cement self-repairing capsule in the self-repairing of high temperature resistant oil well cement.
[0017] As another aspect of the present invention, it relates to a high temperature resistant oil well cement self-repairing system, which is obtained by mixing a high temperature self-repairing agent curing agent with the above-mentioned high temperature resistant oil well cement self-repairing capsule in a mass ratio of (0.5-1):1.
[0018] The high temperature self-repairing agent curing agent is maleic anhydride, phthalic anhydride or diaminodiphenyl sulfone.
[0019] As another aspect of the present invention, it relates to the application of the above-mentioned high temperature resistant oil well cement self-repairing system in the self-repairing of high temperature resistant oil well cement.
[0020] As another aspect of the present invention, it relates to a cementing slurry, wherein the cementing slurry is prepared by mixing the above-mentioned high temperature resistant oil well cement self-repairing system with G-grade oil well cement in a mass ratio of 4.5-6:95.5-94.
[0021] The invention adopts the O / W / O double emulsion template method to prepare a high-temperature resistant oil well cement self-repairing system with epoxy resin as the repair agent core material and high-temperature resistant polysaccharide as the shell material. The epoxy resin repair agent content can reach more than 46.1%, and the self-repairing efficiency can reach more than 36.57%, so that the self-repairing ability of blank oil well cement can be increased by more than 277.86%, which can effectively improve the self-repairing ability of the cement ring. The initial decomposition temperature of the high-temperature resistant polysaccharide shell material used in the present invention reaches 200°C, so that the high-temperature resistant oil well cement self-repairing system has good high-temperature resistance, can be applied to a variety of complex working conditions, can meet the technical requirements of unconventional oil and gas well cementing, and has a broad application market. (3) The present invention uses natural polysaccharides as shell materials, and the raw materials are widely available, which reduces the pollution of the preparation process, is green and environmentally friendly, and the shell material synthesis process avoids the heating process. The preparation method is simple, the cost is low, and it has the potential for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1The scanning electron microscope image and X-ray energy spectrum analysis image of a high-temperature resistant oil well cement self-repairing capsule of a high-temperature resistant oil well cement self-repairing system prepared in Example 1. Among them, (a) is a surface morphology image of the self-repairing capsule; (b) is a local enlarged image of the surface of the self-repairing capsule; (c) is a C element distribution image; (d) is an O element distribution image; (e) is a Zn element distribution image; (f) is an Al element distribution image. From a and b, it can be seen that the high-temperature resistant oil well cement self-repairing capsule is a particle with a rough surface and a large number of protrusions on the surface, with a diameter of about 400 microns. From cf, it can be seen that the high-temperature resistant oil well cement self-repairing capsule of a high-temperature resistant oil well cement self-repairing system is composed of C, O, Zn and Al elements; the C element mainly comes from the shell material; the O element comes from nano-silicon dioxide and the shell material; Zn is mainly distributed in the protrusions, proving that nano-zinc oxide is successfully incorporated into the shell material; the Al element comes from the shell material curing agent.
[0023] Figure 2 This is a thermogravimetric test diagram of a high temperature resistant oil well cement self-repairing capsule of a high temperature resistant oil well cement self-repairing system prepared in control example 3 and examples 1, 2, 3, and 4. Figure 2 a is the thermogravimetric test diagram of Example 1, Figure 2 b is the thermogravimetric test diagram of Example 2, Figure 2 c is the thermogravimetric test diagram of Example 3, Figure 2 d is the thermogravimetric test diagram of Example 4, Figure 2 e is the thermogravimetric test diagram of control example 3. It can be seen from the figure that a high-temperature resistant oil well cement self-repairing capsule of a high-temperature resistant oil well cement self-repairing system has two main thermal decomposition stages. The self-repairing capsule shell material of control example 3 without doping interface enhancer has a thermal decomposition stage of 120-250°C, and the initial decomposition temperature is only 148.3°C; while the thermal decomposition stage of the self-repairing capsule shell material of embodiments 1-4 is about 200-315°C, and decomposition begins at around 200°C, with better high temperature resistance. The thermal decomposition stage of phenolic epoxy resin is 315-430°C, and the content of phenolic epoxy resin repair agent in high-temperature resistant oil well cement self-repairing capsules decreases as the oil-water ratio decreases. When the oil-water ratio is 50:50-75:25, the repair agent content reaches 45.2-46.1%.
[0024] Figure 3 The compressive strength of the cement matrix of a high-temperature resistant oil well cement self-repairing system prepared by adding reference examples 1, 3 and examples 1-4. Compared with reference example 1, the addition of self-repairing capsules in examples 1-4 will weaken the compressive strength of the cement matrix. This is because the self-repairing capsules form pores in the cement matrix, causing stress defects, but it can still meet the engineering requirements. However, compared with reference example 3, doping the self-repairing capsule shell material with an interface enhancer can effectively compensate for the adverse effects of the self-repairing capsule on the mechanical properties of the cement matrix, which is due to the reaction between the interface enhancer and the cement matrix.
[0025] Figure 4 The compressive strength and repair rate of the cement matrix of a high-temperature resistant oil well cement self-repairing system prepared by adding reference examples 1, 2 and examples 1-4. The calculation formula of the repair rate is: η = (σ2-σ1) / σ1. In the formula: η is the repair rate; σ2 is the compressive strength after repair; σ1 is the compressive strength before repair. The repair rate of Examples 1-4 decreases with the decrease of the oil-water ratio. Compared with reference example 1, the repair rates of Examples 1, 2, and 4 increase, and the repair rate of Example 3 decreases. This is because the microcapsules form more pores in the cement matrix. When the content of phenolic epoxy resin is too low to effectively repair the cracks, the external fluid further erodes the cement matrix along the pores, resulting in a lower compressive strength after repair (the same is true for the low self-repair efficiency of Example 7 in Table 1). Compared with Examples 1-4, the repair rate of Reference Example 2 is lower. This is because there is no high-temperature self-repairing agent curing agent in Reference Example 2, and the phenolic epoxy resin cannot be cured at all, and has no repair effect on the cracks. The external fluid erodes along the pores, causing the repair rate to further decrease. In summary, when the oil-water ratio of the self-healing capsule is 50:50-75:25, the repair rate is 36.11%-36.57%, and the repair effect is the best. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0027] The G-grade oil well cement used in the following embodiments is produced by Sichuan Jiahua Enterprise Co., Ltd., nano zinc oxide is purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., and is a nano zinc oxide product of model XFI06-1 with a particle size of 50-100 nanometers, gelatin is provided by Shanghai Aladdin Biochemical Technology Co., Ltd., and is a product with a molecular weight between 50,000 and 100,000, carrageenan is provided by Sigma-Aldrich Trading Co., Ltd., and is a carrageenan product with a molecular weight between 200,000 and 800,000, and silica sol is provided by Kehan Silica Products Co., Ltd., and is a silica sol of model KH-715 with a particle size of 7-10 nanometers, but this is not intended to limit the present invention.
[0028] The high temperature resistant oil well cement self-repairing capsule of the high temperature resistant oil well cement self-repairing system prepared in Example 1 was observed and analyzed using a scanning electron microscope and an X-ray spectrometer. Figure 1 The high temperature resistant oil well cement self-repairing capsules of the high temperature resistant oil well cement self-repairing system prepared in the control example 3 and the examples 1, 2, 3 and 4 were heated at a rate of 10°C / min in a temperature range of 25-800°C under a nitrogen atmosphere and measured and analyzed using a thermogravimetric analyzer. Figure 2; After curing the cement matrix of a high temperature resistant oil well cement self-repairing system prepared by adding control examples 1, 3 and examples 1-4 in a curing box at 90°C ± 2°C for 7 days, the compressive strength was tested according to GB / T 19139-2012, and the result was Figure 3 ; A high temperature resistant oil well cement self-repairing system cement matrix prepared by adding control examples 1, 2 and examples 1-4 was pre-cracked according to 90% compressive strength after curing in a curing box at 90℃±2℃ for 7 days, and repaired in a curing box at 90℃±2℃ for 7 days. The compressive strength before and after the repair was tested, and the results were as follows: Figure 4 .
[0029] Example 1
[0030] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0031] Step 1) Preparation of shell material aqueous phase: 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) are added into 100g deionized water and stirred evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0032] Step 2) Preparation of repair agent oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0033] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 50:50, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0034] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0035] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0036] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0037] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 45.2% and the content of the shell material is 54.8%.
[0038] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) with the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0039] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days to test the self-repairing performance of the cement matrix. The results showed that the self-repairing capsule coverage was 82.5%, the initial thermal decomposition temperature was 194.1℃, the compressive strength of the cement matrix was 36.20MPa, and the repair rate was 36.11%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 4.5:95.5.
[0040] Example 2
[0041] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0042] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0043] Step 1) Preparation of shell material aqueous phase: 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) are added to 100g deionized water and stirred evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0044] Step 2) Preparation of repair agent oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0045] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 25:75, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0046] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0047] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0048] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0049] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 23.4% and the content of the shell material is 76.6%.
[0050] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) and the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0051] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G-grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90°C±2°C for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 91.6%, the initial thermal decomposition temperature was 209.1°C, the cement matrix compressive strength was 35.13MPa, and the repair rate was 10.30%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G-grade oil well cement was 4.5:95.5.
[0052] Example 3
[0053] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0054] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0055] Step 1) Preparation of shell material aqueous phase: 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) are added to 100g deionized water and stirred evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0056] Step 2) Preparation of repair agent oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0057] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 20:80, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0058] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0059] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0060] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0061] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 17.9% and the content of the shell material is 82.1%.
[0062] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) and the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0063] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 97.4%, the initial thermal decomposition temperature was 212.4℃, the cement matrix compressive strength was 34.49MPa, and the repair rate was -0.30%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 4.5:95.5.
[0064] Example 4
[0065] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0066] Step 1) Preparation of shell material aqueous phase: Add 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) into 100g deionized water and stir evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0067] Step 2) Preparation of oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain a repairing agent oil phase 1;
[0068] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 75:25, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0069] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0070] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0071] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0072] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 46.1% and the content of the shell material is 53.9%.
[0073] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) and the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0074] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G-grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90°C±2°C for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 28.5%, the initial thermal decomposition temperature was 200.8°C, the cement matrix compressive strength was 34.97MPa, and the repair rate was 36.57%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G-grade oil well cement was 4.5:95.5.
[0075] Example 5
[0076] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0077] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0078] Step 1) Preparation of shell material aqueous phase: Add 20g aluminum carbonate (acid-triggered curing agent), 6g silica sol (interface enhancer) and 6g gelatin (high temperature resistant shell material) into 100g deionized water and stir evenly to obtain shell material aqueous phase, wherein the silica sol used is a product with a particle size of 7-10 nanometers and a model of KH-715, and the gelatin is a product with a molecular weight of 50000-100000;
[0079] Step 2) Preparation of repair agent oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0080] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 50:50, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0081] Step 4) Preparation of oil phase 2: Add 20 g of Span-85 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0082] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0083] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0084] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with silica sol doped with gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 39.8% and the content of the shell material is 60.2%.
[0085] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) and the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0086] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G-grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90°C±2°C for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 65.9%, the initial thermal decomposition temperature was 185.7°C, the cement matrix compressive strength was 29.65MPa, and the repair rate was 28.33%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G-grade oil well cement was 4.5:95.5.
[0087] Example 6
[0088] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0089] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0090] Step 1) Preparation of shell material aqueous phase: Add 40g aluminum carbonate (acid-triggered curing agent), 10g nano zinc oxide (interface enhancer) and 6g gelatin (high temperature resistant shell material) into 100g deionized water and stir evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0091] Step 2) Preparation of repair agent oil phase 1: Add 25 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of bisphenol S epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0092] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 25:75, and stir at 4000 rpm to obtain a uniform oil / water emulsion;
[0093] Step 4) Preparation of oil phase 2: Add 30 g of Span-20 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0094] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 75:25, and stir at 700 rpm to obtain a uniform oil / water / oil template emulsion;
[0095] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute sulfuric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0096] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and bisphenol S epoxy resin as core material, wherein the content of the core material is 20.2% and the content of the shell material is 79.8%.
[0097] Step (2) physically mixes phthalic anhydride (high temperature self-repairing agent curing agent) with the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 0.5:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0098] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 75.9%, the initial thermal decomposition temperature was 145.6℃, the cement matrix compressive strength was 37.88MPa, and the repair rate was 10.79%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 6:94.
[0099] Example 7
[0100] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0101] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0102] Step 1) Preparation of shell material aqueous phase: Add 20g aluminum hydroxide (acid-triggered curing agent), 6g silica sol (interface enhancer) and 4g carrageenan (high temperature resistant shell material) into 100g deionized water and stir evenly to obtain shell material aqueous phase. The silica sol used is a product with a particle size of 7-10 nanometers and a model of KH-715, and the carrageenan is a product with a molecular weight of 200,000-800,000;
[0103] Step 2) Preparation of repair agent oil phase 1: Add 27 g of phenyl glycidyl ether (active diluent) to 100 g of aliphatic epoxy resin (cement self-healing agent), stir evenly, and obtain the repair agent oil phase 1;
[0104] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 20:80, and stir at 5000 rpm to obtain a uniform oil / water emulsion;
[0105] Step 4) Preparation of oil phase 2: Add 25 g of Span-85 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0106] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 75:25, and stir at 750 rpm to obtain a uniform oil / water / oil template emulsion;
[0107] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: drip glacial acetic acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, freeze-dry, and obtain high temperature resistant oil well cement self-repairing capsules.
[0108] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with silica sol doped with carrageenan as shell material and aliphatic epoxy resin as core material, wherein the content of the core material is 16.2% and the content of the shell material is 83.8%.
[0109] Step (2) physically mixes diaminodiphenyl sulfone with the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 0.75:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0110] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 77.3%, the initial thermal decomposition temperature was 130.5℃, the cement matrix compressive strength was 28.75MPa, and the repair rate was -3.27%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 5:95.
[0111] Example 8
[0112] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0113] Step 1) Preparation of shell material aqueous phase: Add 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) into 110g deionized water and stir evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0114] Step 2) Preparation of oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 90 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain a repairing agent oil phase 1;
[0115] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 75:25, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0116] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 90 g of paraffin oil and stir well to obtain oil phase 2;
[0117] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0118] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0119] The obtained high temperature resistant oil well cement self-repairing capsule component is a microcapsule with nano zinc oxide doped gelatin as shell material and phenolic epoxy resin as core material, wherein the content of the core material is 44.7% and the content of the shell material is 55.3%.
[0120] Step (2) physically mixes maleic anhydride (high temperature self-repairing agent curing agent) and the high temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1 to obtain a high temperature resistant oil well cement self-repairing system.
[0121] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 30.6%, the initial thermal decomposition temperature was 202.3℃, the cement matrix compressive strength was 32.76MPa, and the repair rate was 35.95%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 4.5:95.5.
[0122] Comparative Example 1:
[0123] The high temperature resistant oil well cement self-healing system is not used.
[0124] Construction of blank cement system. According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: G-grade oil well cement was added to tap water to obtain a blank cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days. The self-healing performance of the blank cement matrix was tested. The results showed that the compressive strength of the cement matrix was 44.24MPa and the repair rate was 9.68%. Among them, the mass ratio of the high temperature resistant oil well cement self-healing system to the G-grade oil well cement was 0:100.
[0125] Comparative Example 2:
[0126] Refer to Example 1, except that high temperature self-healing curing agent such as maleic anhydride, phthalic anhydride or diaminodiphenyl sulfone is not used.
[0127] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0128] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0129] Step 1) Preparation of shell material aqueous phase: 10g aluminum carbonate (acid-triggered curing agent), 4g nano zinc oxide (interface enhancer) and 3g gelatin (high temperature resistant shell material) are added into 100g deionized water and stirred evenly to obtain shell material aqueous phase, wherein the nano zinc oxide used is a product with a particle size of 50-100 nanometers and a model of XFI06-1, and the gelatin is a product with a molecular weight of 50000-100000;
[0130] Step 2) Preparation of oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain a repairing agent oil phase 1;
[0131] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 50:50, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0132] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0133] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0134] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0135] In step (2), the high temperature resistant oil well cement self-repairing capsules obtained in step (1) are directly mixed to form a high temperature resistant oil well cement self-repairing system.
[0136] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G-grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90°C±2°C for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 82.5%, the initial thermal decomposition temperature was 194.1°C, the cement matrix compressive strength was 33.66MPa, and the repair rate was -16.56%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G-grade oil well cement was 4.5:95.5.
[0137] Comparative Example 3:
[0138] Refer to Example 1, except that no interface enhancer such as nano zinc oxide or silica sol is used.
[0139] A high temperature resistant oil well cement self-repairing system and preparation method and application thereof, comprising the following steps:
[0140] Step (1) Preparation of high temperature resistant oil well cement self-repairing capsules:
[0141] Step 1) Preparation of shell material aqueous phase: Add 10g aluminum carbonate (acid-triggered curing agent) and 3g gelatin (high temperature resistant shell material) into 100g deionized water, stir evenly, and obtain shell material aqueous phase, wherein gelatin has a molecular weight of 50000-100000;
[0142] Step 2) Preparation of oil phase 1: Add 20 g of polypropylene glycol diglycidyl ether (active diluent) to 100 g of phenolic epoxy resin (cement self-healing agent), stir evenly, and obtain a repairing agent oil phase 1;
[0143] Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 50:50, and stir at 6000 rpm to obtain a uniform oil / water emulsion;
[0144] Step 4) Preparation of oil phase 2: Add 20 g of Span-80 (surfactant) to 100 g of paraffin oil and stir well to obtain oil phase 2;
[0145] Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 80:20, and stir at 800 rpm to obtain a uniform oil / water / oil template emulsion;
[0146] Step 6) Forming high temperature resistant oil well cement self-repairing capsules: Add dilute hydrochloric acid (trigger) drop by drop into the oil / water / oil template emulsion obtained in step 5), stir until the droplets are fixed, centrifuge, wash with deionized water, and freeze-dry to obtain high temperature resistant oil well cement self-repairing capsules.
[0147] Step (2) physically mixes maleic anhydride (high-temperature self-repairing agent curing agent) and the high-temperature resistant oil well cement self-repairing capsule obtained in step (1) at a mass ratio of 1:1.
[0148] According to the standard GB / T 19139-2012, a cement slurry with a water-cement ratio of 0.44 was prepared: the high temperature resistant oil well cement self-repairing system prepared in this embodiment was first added to tap water, and after absorbing water for 5 minutes, G grade oil well cement was added to obtain a cement slurry system, and cured in a curing box at 90℃±2℃ for 7 days, and the self-repairing performance of the cement matrix was tested. The results showed that the self-repairing capsule coverage rate was 82.5%, the initial thermal decomposition temperature was 194.1℃, the cement matrix compressive strength was 22.46MPa, and the repair rate was 34.11%. Among them, the mass ratio of the high temperature resistant oil well cement self-repairing system to the G grade oil well cement was 4.5:95.5.
[0149] Performance Evaluation
[0150] Table 1 Parameters and properties of different self-repairing microcapsules
[0151]
[0152] Table 2 Cost calculation of different self-repairing microcapsules
[0153] serial number Shell material water phase cost Core material oil phase cost Total Cost Example 1 15.6 yuan / L 19.9 yuan / L 88.75 yuan / kg microcapsule Example 2 15.6 yuan / L 19.9 yuan / L 167.93 yuan / kg microcapsule Example 3 15.6 yuan / L 19.9 yuan / L 205.75 yuan / kg microcapsule Example 4 15.6 yuan / L 19.9 yuan / L 125.50 yuan / kg microcapsule Example 5 27.1 yuan / L 19.9 yuan / L 117.50 yuan / kg microcapsule Example 6 36.3 yuan / L 24.1 yuan / L 335.25 yuan / kg microcapsule Example 7 23.6 yuan / L 33.4 yuan / L 319.50 yuan / kg microcapsule Example 8 14.6 yuan / L 18.3 yuan / L 112.80 yuan / kg microcapsule García Calvo et al. 63.4 yuan / L 78.13 Yuan / L 1783.76 yuan / kg microcapsule Ma et al. 68.8 yuan / L 46.6 yuan / L 622.1 yuan / kg microcapsule
[0154] Table 1 shows the process parameters, coverage rate and performance of a high-temperature resistant oil well cement self-repairing capsule of a high-temperature resistant oil well cement self-repairing system prepared in Examples 1-7. The formula for calculating the coverage rate is: Q=m2 / m1. Wherein: Q is the coverage rate; m2 is the mass of the self-repairing agent coated in the self-repairing capsule; m1 is the mass of the self-repairing agent added during the synthesis of the self-repairing capsule. At the same oil-water ratio, compared with Examples 5-7, the coverage rate of Example 1-3 is higher. This is because the shell material acid trigger system of Example 1-3 is more efficient and the emulsifier has better compatibility with the system, and the coverage rate reaches 82.5%-97.4%. Compared with Examples 5 and 7, the self-healing capsules of Examples 1-4 and 6 have less effect on the compressive strength performance of the cement matrix. This is because the nano-zinc oxide doping reacts with the cement matrix to generate zinc hydroxide, which compensates for the decrease in the compressive strength of the cement matrix; Examples 1, 4, and 5 have higher self-healing efficiency. This is because the self-healing capsules have a lower oil-water ratio, and the capsules contain more self-healing agents, which can effectively seal cracks; Compared with Examples 5-7, Example 1-4 has a high initial decomposition temperature and good thermal stability. This is because the thermal decomposition temperature of gelatin is relatively high and the nano-zinc oxide has good thermal stability. The two form an organic-inorganic cross-linking system, which further improves the thermal stability of the shell material.
[0155] Table 2 is a cost calculation table of a high temperature resistant oil well cement self-repairing capsule of a high temperature resistant oil well cement self-repairing system prepared in Examples 1 to 7. Compared with Examples 5 to 7, the water phase and oil phase costs of Examples 1 to 4 are lower, among which the total cost of Example 1 is the lowest, which is 88.75 yuan / kg microcapsule.
[0156] It can be seen from the examples that the coating rates of Examples 1-3 are higher because aluminum carbonate is selected as the acid-triggered curing agent, dilute hydrochloric acid is used as the trigger, and Span-80 is used as the surfactant. The emulsified systems have better compatibility and the shell material has better water-phase coating performance.
[0157] The cost of Examples 1, 4, and 5 is lower because gelatin is selected as the high temperature resistant shell material and phenolic epoxy resin is selected as the self-healing agent core material, which has a lower cost;
[0158] Examples 1-7 are green and environmentally friendly because gelatin or carrageenan is selected as the high temperature resistant shell material, the shell material is derived from biological materials and the synthesis process avoids the heating process, which is simple and efficient, and has the advantages of being green, environmentally friendly and easy to synthesize;
[0159] The self-repairing capsule shell material of Example 1-4 has better thermal stability because nano zinc oxide is selected as the interface enhancer and gelatin is used as the high temperature resistant shell material. Nano zinc oxide and gelatin form an organic-inorganic composite shell material with better high temperature resistance.
[0160] The content of the repair agent in Examples 1 and 4 is higher because the volume ratio of oil to water in the oil / water emulsion is controlled to be 50:50-75:25, which ensures the content of the self-repairing agent in the self-repairing capsule;
[0161] The damage to the compressive strength of the cement matrix in Examples 1-4 and 6 is relatively small because nano zinc oxide is selected as the interface enhancer, and the reaction between nano zinc oxide and the cement matrix effectively compensates for the adverse effects of the self-repairing capsules on the mechanical properties of the cement matrix;
[0162] The good repair performance of Examples 1, 4, and 5 is due to the use of maleic anhydride as a high-temperature self-repairing agent curing agent, and the control of the volume ratio of oil to water in the oil / water emulsion to 50:50-75:25, so that the content of self-repairing agent in the high-temperature resistant oil well cement self-repairing capsules is relatively high and can effectively cure and fill cracks, giving the cement matrix good self-repairing ability; the repair rate of Examples 3 and 7 is lower than that of Control Example 1. This is because the oil-water volume ratio is 20:80, the content of self-repairing agent in the self-repairing capsules is low and cannot effectively repair cracks, and the microcapsules form more pores in the cement matrix, and the external fluid further erodes the cement matrix along the pores, resulting in lower compressive strength after repair.
[0163] Based on the evaluation results, the comprehensive results of Examples 1, 4, and 5 are better. The reagent selection and parameter selection are summarized as 10g-20g of aluminum carbonate, 4g-6g of interface enhancer, 3g-6g of gelatin, the oil-water ratio in the oil / water emulsion is between 50:50-75:25, and the mass ratio of the high-temperature self-healing agent curing agent to the high-temperature resistant oil well cement self-healing capsule is between (0.5-1):1.
[0164] In summary, the high temperature resistant oil well cement self-repairing system of the present invention has significant self-repairing ability, which effectively solves the shortcomings of traditional oil well cement self-repairing systems such as high pollution, high cost, difficulty in industrialization, and poor high temperature resistance.
[0165] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high temperature resistant oil well cement self-repairing capsule, characterized in that: The high temperature resistant oil well cement self-repairing capsule uses high temperature resistant polysaccharide as shell material and epoxy resin as core material, wherein the content of the core material is 15%-50%, and the content of the shell material is 85-50%.
2. The method for preparing the high temperature resistant oil well cement self-repairing capsule according to claim 1, characterized in that: Includes steps: Step 1) Preparation of shell material aqueous phase: Add 10-40g of acid-triggered curing agent, 4-10g of interface enhancer and 3-6g of high temperature resistant shell material into 100-110g of water, stir evenly to obtain shell material aqueous phase; Step 2) Preparation of repair agent oil phase 1: Add 20-27 g of active diluent to 90-100 g of cement self-repairing agent, stir evenly, and obtain repair agent oil phase 1; Step 3) Preparation of oil / water emulsion: Mix the repair agent oil phase 1 obtained in step 2) and the shell material water phase obtained in step 1) at a volume ratio of 20-75:80-25 to obtain a uniform oil / water emulsion; Step 4) Preparation of oil phase 2: Add 20-30 g of surfactant to 90-100 g of paraffin oil and stir evenly to obtain oil phase 2; Step 5) Preparation of oil / water / oil template emulsion: Mix the oil phase 2 obtained in step 4) and the oil / water emulsion obtained in step 3) at a volume ratio of 75-80:25-20 to obtain a uniform oil / water / oil template emulsion; Step 6) Forming high temperature resistant oil well cement self-repairing capsules: dripping the triggering agent drop by drop into the oil / water / oil template emulsion obtained in step 5), stirring until the droplets are formed, and obtaining high temperature resistant oil well cement self-repairing capsules.
3. The method for preparing the high temperature resistant oil well cement self-repairing capsule according to claim 1 according to claim 2, characterized in that: In the step 1), the acid-triggered curing agent is aluminum carbonate or aluminum hydroxide; the interface enhancer is nano zinc oxide or silica sol; and the high temperature resistant shell material is gelatin or carrageenan.
4. The method for preparing the high temperature resistant oil well cement self-repairing capsule according to claim 1 according to claim 2, characterized in that: In the step 2), the active diluent is polypropylene glycol diglycidyl ether or phenyl glycidyl ether; and the cement self-healing agent is phenolic epoxy resin, bisphenol S epoxy resin or aliphatic epoxy resin.
5. The method for preparing the high temperature resistant oil well cement self-repairing capsule according to claim 1 according to claim 2, characterized in that: In the step 4), the surfactant is Span-80, Span-20 or Span-85; and the trigger is dilute hydrochloric acid, dilute sulfuric acid or glacial acetic acid.
6. Use of the high temperature resistant oil well cement self-repairing capsule according to claim 1 in the self-repairing of high temperature resistant oil well cement.
7. A high temperature resistant oil well cement self-repairing system, characterized in that: The high temperature resistant oil well cement self-repairing system is obtained by mixing a high temperature self-repairing agent curing agent with the high temperature resistant oil well cement self-repairing capsule according to claim 1 in a mass ratio of (0.5-1):
1.
8. The high temperature resistant oil well cement self-repairing system according to claim 7, characterized in that: The high temperature self-repairing agent curing agent is maleic anhydride, phthalic anhydride or diaminodiphenyl sulfone.
9. Use of the high temperature resistant oil well cement self-repairing system according to any one of claims 7 or 8 in the self-repairing of high temperature resistant oil well cement.
10. A cementing slurry, characterized in that: The cementing slurry is prepared by mixing the high temperature resistant oil well cement self-repairing system according to any one of claims 7 and 8 and Class G oil well cement in a mass ratio of 4.5-6:95.5-94.
Citation Information
Cited By
Cement temperature inhibition and crack self-repairing microcapsule as well as preparation method and application thereof
CN121913726A
Cement temperature inhibition and crack self-repairing microcapsule, preparation method and application thereof
CN121913726B